Dormant pathogenic CD4+ T cells are prevalent in the peripheral repertoire of healthy mice - Anna Cebula (Nature Portfolio, 2019)
Autoreactive T cells are normally eliminated during their maturation in the thymus, but an unknown number of autoreactive CD4+ T cells escape to the periphery. Here the authors show, by comparing the T cell receptors of mice sufficient or deficient in CD4+Foxp3+ regulatory T (Treg) cells, that autoreactive and potentially pathogenic clones account for approximately one-third of the peripheral repertoire of CD4+Foxp3– cells.